Exploiting wild accessions for development of high yielding new rice genotypes - Wickneswari, R.; Bhuiyan, M.A.R. (Penerbit Universiti Kebangsaan Malaysia, 2014)
Eight transgressive variants were selected from a cross between Oryza rufipogon Griff. (IRGC105491) and MR219, a Malaysian high yielding rice cultivar. The field trials revealed the yield potentiality of the variants and showed significantly (p<0.05) higher yield than the control, MR219. Quantitative trait loci (QTLs) for agronomic traits were validated in the selected variants in BC2F5 generation. The yield of these variants was influenced by several QTLs related to days to maturity, tillers per plant, panicles per plant, spikelets per panicle and thousand grain weight. Chromosome segment analysis confirmed the introgression of wild alleles for yield and yield related traits. Registration process for eight variants has been initiated under the National Plant Variety (NPV) Act of Malaysia with the preferred name of UKMRC1 to UKMRC8. The DUS test was conducted in 2011 following UPOV guidelines in collaboration with Department of Agriculture, Malaysia to confirm distinctness, uniformity and stability of these variants. Steps will be taken for some of the promising registered variants to be released as new varieties.